Protocol for a prospective multicenter longitudinal randomized controlled trial (CALIN) of sensory-tonic stimulation to foster parent child interactions and social cognition in very premature infants - Guittard, Cassandre; Novo, Alexandre; Eutrope, Julien; Gower, Corinne; Barbe, Coralie; Bednarek, Nathalie; Rolland, Anne-Catherine; Caillies, Stéphanie; Loron, Gauthier (Frontiers in Pediatrics, 2023)
Introduction: Premature birth is associated with long-term somatic and neurological disorders, including cognitive, social and behavioral impairments. Moreover, the mothers of infants born preterm exhibit a higher prevalence of anxiety and depressive symptoms after birth. Early rehabilitation, developmental care, and parenting support have already been shown to have a positive impact on neurological outcome. However, no randomized controlled study has so far assessed the effects on parenting and long-term neurological outcomes of proprioceptive stimulation to trigger positive brain plasticity in very preterm babies. The CALIN project will therefore investigate the impact of sensory-tonic stimulation (STS) of extremely preterm infants by their parents on child parent interactions, infants’ morphological and functional brain development and subsequent cognition (including social cognition), and parents’ anxiety and depressive symptoms in the postpartum period. Methods and analysis: Infants born between 25 and 32 weeks of gestation will be randomly assigned to the “STS + Kangaroo care” or “Kangaroo care” group. The primary endpoint, child and parent interactions, will be rated at 12 months corrected age using the Coding Interactive Behavior system. Secondary endpoints include: 1/ functional and anatomical brain maturation sequentially assessed during neonatal hospitalization using electroencephalogram (EEG), amplitude-integrated EEG (aEEG), cranial ultrasound and MRI performed at term-corrected age, 2/ social and cognitive outcomes assessed at 15 months, 2, 4 and 6 years, and 3/ parents’ anxiety and depressive symptoms assessed at 7 ± 1 weeks after birth, using dedicated questionnaires. Ethics and dissemination: This study was approved by the French Ethics Committee for the Protection of Persons on 18 October 2021. It is registered with the French National Agency for the Safety of Medicines and Health Products (ANSM; no. 2020-A00382-37). The registry number on ClinicalTrials.gov is NCT04380051.